(untitled) (Mokslo taikomieji tyrimai / Applied Research, 2023)
In contemporary European educational contexts, equal access to education and learning opportunities have become one of the main issues. Socio-economic factors and the surrounding environment are widely recognised as the main barriers to changing an individual’s social position in society, while the disparity between educational opportunities and learning outcomes is seen to be growing. This paper aims to address the ongoing challenges and opportunities to break down barriers to upward mobility and promote equal opportunities for all by looking at different intervention approaches, such as coaching and positive role models. International research involving participants from 6 European countries - Lithuania, Italy, Norway, Greece, Romania and the United Kingdom - was carried out to assess the effectiveness of the coaching method and its impact on unlocking learning potential in the educational setting. The research findings suggest that coaching effectively promotes learning and behavioural change in disadvantaged learners.